2020
DOI: 10.3390/cells9040949
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Endothelial Progenitor Cells in Obese Diabetic Rats Following Myocardial Infarction: Role of Thymosin Beta-4

Abstract: Endothelial progenitor cells (EPCs) are bone-marrow derived cells that are critical in the maintenance of endothelial wall integrity and protection of ischemic myocardium through the formation of new blood vessels (vasculogenesis) or proliferation of pre-existing vasculature (angiogenesis). Diabetes mellitus (DM) and the metabolic syndrome are commonly associated with ischemic heart disease through its pathological effects on the endothelium and consequent endothelial dysfunction. Thymosin-β4 (Tβ4) which expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Consequently, their reparative capacity after infarction is reduced. Treatment of EPC with different molecules such as thymosin beta-4 ( Poh et al, 2020 ) and the overexpression of Sonic hedgehog (Q. Xiao et al, 2019 ) recover the reparative properties of EPC after MI in the context of diabetes by inducing their mobilization (restoring their circulating levels) or promoting angiogenesis.…”
Section: New Insights Of Endothelial-mediated Protection Against Ischmentioning
confidence: 99%
“…Consequently, their reparative capacity after infarction is reduced. Treatment of EPC with different molecules such as thymosin beta-4 ( Poh et al, 2020 ) and the overexpression of Sonic hedgehog (Q. Xiao et al, 2019 ) recover the reparative properties of EPC after MI in the context of diabetes by inducing their mobilization (restoring their circulating levels) or promoting angiogenesis.…”
Section: New Insights Of Endothelial-mediated Protection Against Ischmentioning
confidence: 99%
“…Currently, there is little information on the role of Tb4 on diabetic ECs. Previously, we showed that Tb4 improved migration of CD34 + /KDR + circulating endothelial progenitor cells (EPCs) from diabetic fatty rats [ 23 , 24 ]. Furthermore, in the current study, we aimed to use diabetic-hiPSC-ECs as diabetic EC models to study the role of Tb4 on proliferation, viability, senescence, and angiogenesis of diabetic ECs.…”
Section: Introductionmentioning
confidence: 99%
“…The mingling of pathological mechanisms affecting cardiovascular health is clearly reflected by the risk of CVD associated with metabolic diseases, including conditions such as obesity or diabetes. This connection is explored in several studies of the present volume [ 5 , 15 ]. A link of these factors is studied by Actis-Dato et al in their study of the involvement of LRP-1 in insulin response in a myoblast cell line [ 23 ].…”
mentioning
confidence: 97%
“…Endothelial cells not only are players in CVD, but are also a therapeutic option [ 14 ]. Poh et al [ 15 ] explore the effects of thymosin-β4 (Tβ4) on endothelial progenitor cells (EPCs) in vitro, and in vivo in a diabetic rat model subjected myocardial infarction (MI). In the same field, Kutikhin et al [ 16 ] provide an interesting characterization of endothelial colony-forming cells and its similarity with mature endothelial cells, a topic that has attracted a lot of attention recently, with the publication of several detailed maps of endothelial cell populations that underscore both the versatility of these cellular type and its implications on disease [ 17 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation